Langerhans cell-like dendritic cells stimulated with an adjuvant direct the development of Th1 and Th2 cells in vivo. (21st July 2015) - Matsui, K; Mori, A; Ikeda, R
Summary: It is well known that Langerhans cells (LCs) work as the primary orchestrators in the polarization of immune responses towards a T helper type 1 (Th1) or Th2 milieu. In this study, we attempted to generate LCs from murine bone marrow cells and elicit a Th1- or Th2-prone immune response through the LCs after stimulation with Th1 or Th2 adjuvant. LCs were generated from murine bone marrow cells using granulocyte–macrophage colony-stimulating factor (GM-CSF), interleukin (IL)-4 and transforming growth factor (TGF)-β, and were obtained as I-A d positive cells. Mice were primed with Th1/Th2 adjuvant- and ovalbumin (OVA)-pulsed LCs and then given a booster injection of OVA 2 days later via the hind footpad. Five days after the OVA injection, the cytokine response in the draining popliteal lymph nodes was investigated by reverse transcription–polymerase chain reaction (RT–PCR) flow cytometry and enzyme-linked immunosorbent assay (ELISA). The generated LCs expressed typical LC surface markers, E-cadherin and Langerin, and were classified accordingly as LC-like dendritic cells (LDCs). Administration of Th1 adjuvant, cytosine–phosphate–guanosine (CpG)-DNA- and OVA-pulsed LDCs into the hind footpads of mice induced a Th1-prone immune response, as represented by up-regulation of IFN-γ production and down-regulation of IL-4 production in the lymph node cells. Conversely, Th2 adjuvant, histamine-pulsed LDCs induced a Th2-prone immune response, as represented by up-regulation of IL-4 production and down-regulation of IFN-γ production. These results suggest that LDCs may be used as a substitute for LCs and have the ability to induce the development of Th1 and Th2 cells in vivo . Our experimental system would therefore be useful for screening of inhibitors of Th1/Th2 differentiation in order to control allergic disease.